WHAT MEANS HIGH PERFORMANCE WORK PRACTICES FOR HUMAN RESOURCES IN AN ORGANIZATION? - ANCA-IOANA MUNTEANU (Annals of the University of Petrosani: Economics, 2014)
This paper focused on an overview of the different approaches in the literature to the concept of high performance work practices (HPWP), showing how this term evolves over time. Analyzing the literature, the significance of this term are seen as an evolved with customer requirements. Organizations need employees easily adaptable, able to meet customer needs in a timely manner. Therefore, organizations must on the one hand to satisfy their customers, on the other hand, employees, those in which firms can achieve their goals. Currently have placed particular emphasis on employee motivation, training, their involvement in decision making, delegation of authority, remuneration based on performance, rewarding loyalty. All above are considered HPWP and the AMO model is representative of these. The implementation of HPWP is a current problem for organizations wishing to achieve a sustainable competitive advantage. In this sense, this article may provide information of interest to business.